Pemanfaatan insang ikan tuna (Thunnus sp.) dan lemuru (Sardinella lemuru) sebagai bahan baku pengolahan keripik: Utilization of tuna (Thunnus sp.) and Bali sardinella (Sardinella lemuru) fish gills as raw materials for chips processing - Budiadnyani, I Gusti Ayu; Dewi, Resti Nurmala; Panjaitan, Fenny Crista Anastasia; Febrianti, Desy; Utari, Siluh Putu Sri Dia; Khairunnisa, Anis; Nugraha, I Made Aditya (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Fish gills are low-value by-products of the fisheries industry; however, they are rich in nutrients and have the potential to be developed into value-added products, such as chips. However, as gills act as filters for chemical substances, including heavy metals, food safety is a critical concern. This study aimed to evaluate and compare the characteristics of tuna and Bali sardinella gills in fresh and frozen conditions as raw materials for chips in terms of proximate composition, heavy metal content, microbiological safety, and consumer acceptance. Four treatments were tested: fresh and frozen gills from both tuna and Bali sardinella (duplicates). Proximate analysis included moisture, ash, fat, and protein; heavy metals analysed were Hg, Pb, and Cd. Microbiological tests included total plate count (TPC), Escherichia coli, Salmonella sp., and Vibrio cholerae. Consumer acceptance was evaluated using a hedonic test based on sensory attributes. Raw gills contained 14.15–17.62% protein, 1.61–5.79% fat, 65.36–69.19% moisture, and 10.81–14.93% ash. After processing, the protein content decreased to 8.04–9.52%, whereas the fat content increased to 19.33–26.75%. Moisture and ash also declined to 4.12–4.67% and 4.66–6.19%, respectively. Fresh Bali sardinella gill chips had the highest fat content (26.75%), whereas frozen tuna gill chips had the highest protein content (9.52%). Heavy metal levels remained below the limits set by SNI 7387:2009, and all microbiological parameters complied with the food safety standards. Hedonic testing showed high consumer acceptance, with all products scoring above 8.00 overall, and the highest taste score (8.90) was recorded for frozen tuna gill chips.